Out of the Box Thoughts about the International Financial Architecture - Eichengreen, Barry (Washington, D.C. : International Monetary Fund, 2009)
The Global Credit Crisis of 2008-09 has underscored the urgency of reforming the international financial architecture. While a number of short-term reforms are already in train, this paper contemplates more ambitious reforms of the international financial architecture that might be implemented over the next ten years. It proposes routinizing the expansion of IMF quotas and the conduct of exchange rate surveillance. It contemplates an expanded role for the SDR in international transactions, which would require someone-like the IMF-to act as market maker. It considers proposals for reimposing Glass-Steagall-like restrictions on commercial and investment banking, something that will have to be coordinated internationally to be feasible. Other proposals would require banks to purchase capital insurance; here the question is who would be on the other side of the market. Again there is likely to be a role for the IMF. Then there are arguments for a new agency or institution to deal with cross-border bank insolvencies. Any such entity will require staff support, which might plausibly come from the Fund. Finally, some insist that international colleges of regulators are not enough-that it is desirable to create a World Financial Organization (WFO) with the power to sanction members whose national regulatory policies are not up to international standards. A WFO will similarly need staff support, of which the IMF would be one possible source. All this of course presupposes meaningful IMF governance reform so that the institution has the legitimacy and efficiency to assume these additional responsibilities. The paper therefore concludes with some conventional and unconventional proposals for IMF governance reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet